What Is the Most Appropriate Induction Regimen for the Treatment of HIV-Associated Cryptococcal Meningitis When the Recommended Regimen Is Not Available? Evidence From a Network Meta-Analysis - Li, Yao; Huang, Xiaojie; Qin, Yuanyuan; Wu, Hao; Yan, Xiaofeng; Chen, Yaokai (Frontiers in Pharmacology, 2020)
Aims: Our object was to find the most appropriate, most effective, and most readily available of four induction regimens for HIV-associated cryptococcal meningitis (CM) (Regimen A: 1 week of AmB plus 5-FC followed by 1 week of fluconazole, Regimen B: 1 week of AmB plus fluconazole followed by 1 week of fluconazole, Regimen C: 2 weeks of AmB plus 5-FC, Regimen D: 2 weeks of AmB plus fluconazole), given the vast differences between resource-limited and resource-abundant settings regarding therapeutic drug accessibility, availability, and affordability for HIV-associated (CM). Methods: We conducted a network meta-analysis to compare the therapeutic efficacy and safety of four different induction treatment regimens. Results: The 10-week mortality of Regimen A was significantly lower than that of Regimen B and D, and the 2-week mortality of Regimen A was significantly lower than that of Regimen B. Furthermore, there were no statistically significant differences in 10-week mortality, 2-week mortality, as well as in effective fungicidal activity (EFA) over the first 2 weeks among Regimen B, C and D. The statistical differences in adverse events between Regimen B and Regimen D, and Regimen C and Regimen D were not calculated to be significant. Conclusions: Our results indicate that, 1 week of AmB plus 5-FC followed by 1 week of fluconazole is superior to the three other studied regimens, and that when 5-FC is not available, accessible or affordable, 2 weeks of AmB plus fluconazole or 1 week of AmB plus fluconazole followed by 1 week of fluconazole is an appropriate substitution for 2 weeks of AmB plus 5-FC.